Exploring Genitourinary Syndrome of Menopause: Analysis of Prevalence, Determinants, and Health Impacts in Pakistani Women : Genitourinary Syndrome of Menopause - Ismail, Ayesha; Bibi, Iqra (Pakistan BioMedical Journal, 2024)
The genitourinary syndrome of menopause (GSM) is a common and complicated medical illness suffered by females after menopause. The current study studied its clinical manifestations, etiological factors, and their impact on the quality of life. Objective: To evaluate the prevalence of GSM in Pakistani women of Rural Health Centre, Kangra, District Haripur and the causes associated with the symptoms and play a role in the worsening of disease. Methods: An observational cross-sectional study was conducted in Rural Health Center, Kangra, District Haripur, Khyber Pakhtunkhwa, Pakistan, from 1 January 2023 to 30 June 2023, for six months. It involved 202 women aged 35-55 years. Results: The observations involved the variables, including demographics of patients, clinical parameters associated with GSM and medical comorbidities. Hypertension and diabetes mellitus were identified as the most prevalent diseases in GSM-suffering females. Conclusions: The variables strongly impact women’s health and quality of life after menopause. The prevalence of certain comorbidities and their pattern related to GSM shed light on the importance of targeted healthcare strategies and preventive measures for females.